Factors Influencing Consumer’s Choice of Streaming Over the top (OTT) Platforms (Indian Journal of Extension Education, 2021)
With the rapid advancement in technology, penetration of smart phones and increase in levels of affordable internet facilities resulted in the rise of OTT media services. OTT platforms gives freedom to their users to watch T.V. series, movies, etc.at their own convenience. The study was conducted to find out the factors influencing consumer’s choice of streaming OTT platforms. Convenience sampling technique was used for the study and response from 200 respondents (students, working people/ staff, homemakers and entrepreneurs), was collected in Hisar city, through semi-structured questionnaire. The variations in the factors (Growth, Benefits of OTT, Integrated marketing and communication) were 41.321, 6.621, 5.977, and 5.378 per cent, respectively. As per factor analysis, all four factors were most important that influenced consumers’ choice of streaming OTT services, and the Cronbach alpha values were 0.844, 0.812, 0.798 and 0.629, respectively.